New vocabulary in the lexicon Between the methodology of the ancients and the vision of Dusi in the Mstdrkh - Yassen, Malek (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The most recent linguists have been concerned about the linguistic interests of the Arab linguists since early on. Most of the old linguists, including the owners of the dictionaries, remained alone outside the walls of the lexicons because they were convinced that the linguistic dictionary according to the standard of linguistic protest in the Arab environment was not the appropriate place. Has proved that a large number of them began to penetrate into the entity of the lexicon language in one way or another, and some of these words have brought new scientific or conceptual connotations. The modern era has seen many lexicographic works that have multiple purposes: additions, completions, or attempts to develop the Arabic lexicon. The most important of these attempts was presented by the Dutch orientalist Reinhard Douzy in his work "Supplementing the Arabic Dictionaries". He tried to present a new methodology in the mechanism of induction, selection and classification, far from the lexicon of the linguistic protest age circle.